Recent brachiopods from the South China Sea, NW Pacific - Bitner, Maria Aleksandra; Romanin, Marco (Zootaxa, 2017)
Three articulated brachiopod species have been recognized in material collected during the 2014 French-Taiwanese cruise DongSha to the South China Sea, NW Pacific: Terebratulina japonica (Sowerby, 1846), Macandrevia sp. and Nipponithyris afra Cooper, 1973. Nipponithyris afra is noted for the first time from the Northern Hemisphere and the genus Macandrevia is reported for the first time from the West Pacific. All species are reported for the first time from the South China Sea, extending their biogeographical range.